TRANSITIVITAS DALAM TEKS BANGKE OROS DAN RELEVANSINYA TERHADAP PEMBELAJARAN BAHASA DI SMA - Lukmanul Hakim (Balai Bahasa Nusa Tenggara Barat, 2016)
This research is aimed at describing transitivity system in the Bangke Oros text, the value within the text, and its’ relevancy toward Indonesian teaching and learning at senior high school. Data were gathered using library research using reading and a note taking technique. Data were mainly taken from the Bangke Oros text. The descriptive qualitative and quantitative approaches were used to analyze the data. The analysis employed an identification technique and both formal and informal methods. The result shows that (1) transitivity system on the text of Bangke Oros covered three functions: i.e. process, participant, and circumstance. In according with the functions, process was dominated by realization process. The participants consisted of participants I and II. Participant I was dominated by the one who involved and participants II was dominated by identity. Circumstance is dominated by location. (2) the values in Bangke Oros text consisted of creating, the power of God, defencelessness, awareness and obedience. (3) its’ contribution is focused on the suitability of the text of Bangke Oros into teaching and learning material and application of transitivity system in the teaching and learning of Indonesian language.